Cosmianthemum melinhense (Acanthaceae), a new species from the Me Linh Station for Biodiversity in northeastern Vietnam - Hai, Do Van; Cuong, Nguyen The; Choudhary, Ritesh Kumar; Lin, Zheli; Deng, Yunfei (Phytotaxa, 2022)
Cosmianthemum melinhensis, a new species of Acanthaceae is described and illustrated from northern Vietnam. It is morphologically allied to C. guangxiense, C. knoxiifolium, and C. viriduliflorum but differs in the habit, shape and trichomes of the leaves, stem, bracts, bracteole, corolla and fruits. This species is assessed as “Vulnerable” (VU) according to IUCN Red List Categories and Criteria.